1995
DOI: 10.1017/s0950268800058349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PFGE, ribotyping and phage-typing in the epidemiological analysis ofCampylobacter jejuniserotype HS2 infections

Abstract: SUMMARYIn this study we have evaluated the ability of three typing methods, pulsed field gel electrophoresis (PFGE), phage-typing and ribotyping, to discriminate not only between strains of differing serotypes but also between strains within a single serotype, heat stable serotype 2 (HS2). Forty-five isolates derived from cases of campylobacter enteritis occurring in the Cardiff area were examined. These included 18, mostly HS2, strains associated with an outbreak. The typing results for these and a further 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
2
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 13 publications
7
83
2
3
Order By: Relevance
“…have been described elsewhere [18], and our study confirms the potential for this technique. However, we observed only a single Hae III ribotype pattern for the majority of serogroup HS 1, 2 and 4 strains in this study (Tables 2a-c), a similar finding to that reported elsewhere [2,5]. These three serogroups account for up to 80% of all serogroupable human isolates [17], and HaeIII ribotyping appears inadequate for subtyping this group.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…have been described elsewhere [18], and our study confirms the potential for this technique. However, we observed only a single Hae III ribotype pattern for the majority of serogroup HS 1, 2 and 4 strains in this study (Tables 2a-c), a similar finding to that reported elsewhere [2,5]. These three serogroups account for up to 80% of all serogroupable human isolates [17], and HaeIII ribotyping appears inadequate for subtyping this group.…”
Section: Discussionsupporting
confidence: 87%
“…Our results with the E3CJC2 probe, using a limited panel of strains, also found variability within these groups, particularly amongst strains of HS 1 (Table 2a). No genotype variation was detected amongst the HS 2/HL 4 strains examined in this study, contrary to the variability reported elsewhere [2,3,21]. However, our analysis is restricted to strains showing the defined stable antigenic associations predominating in human infections (e.g.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…[205] and Campylobacter spp. [206,207]. rDNA based fingerprints can be obtained also by ARDRA (Amplified rDNA restriction analysis).…”
Section: Typingmentioning
confidence: 99%